2020
DOI: 10.1371/journal.pone.0239274
|View full text |Cite
|
Sign up to set email alerts
|

Family meal frequency and its association with food consumption and nutritional status in adolescents: A systematic review

Abstract: This systematic review evaluated the association between frequency of family meals (FFM) and nutritional status (NS) and/or food consumption (FC) in adolescents. The protocol was registered with PROSPERO (CRD42017062180) and followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. No publication date, language, or meal type restrictions were imposed. Only full-text original articles were included; qualitative studies were excluded. Studies were identified by searching 5 elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 63 publications
(356 reference statements)
0
25
0
2
Order By: Relevance
“…Hence, a balanced nutritional pattern can create a robust immune foundation. Rhaisa et al [16] revealed that staple foods containing carbohydrates are often consumed and have been part of Indonesia's culture for a long time. Carbohydrates are one of the primary sources of energy for the body.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, a balanced nutritional pattern can create a robust immune foundation. Rhaisa et al [16] revealed that staple foods containing carbohydrates are often consumed and have been part of Indonesia's culture for a long time. Carbohydrates are one of the primary sources of energy for the body.…”
Section: Discussionmentioning
confidence: 99%
“…Briawan et al [22] explained in their research that most adolescents 15-24 years had not met their fluid needs according to the recommendation to drink eight glasses of water per day. Students' lack of drinking water frequency is because teenagers currently only consume water when thirsty [16]. The impact of lack of fluids on the body is fatigue and makes the body weak and loses focus and lowers the body's metabolic conditions [22].…”
Section: Discussionmentioning
confidence: 99%
“…Current discussion around commensality within households tends to focus on the location where people choose to eat, for example, in front of the TV or at the table, and whether the change of location leads to nutritionally unfavorable food choices or not [31]. Food choice in regards to eating together or alone has not been extensively studied, but some publications have pointed to a risk of less healthy meals among older adults who have become widowed [24] and thus may eat alone, and several to associations between family-meal participation frequency and food intake among children [32]. There are also examples of evidence to the contrary, with less healthy choices of food and drink sometimes occurring when eating together, for example during weekends, enjoying extra meals for their aesthetic pleasure, or having meals just to keep company, as indicated by the latest National Food Survey in Sweden [33], or during workplace breaks [34,35].…”
Section: Introductionmentioning
confidence: 99%
“…Socio economic status was explored in 13 studies (Bau et al, 2011;Chartatos et al, 2018;Fleary et al, 2018;Ghasab et al, 2017;Gracey et al, 1996;Nagy-Pénzes et al, 2020;Park et al, 2013;Pearson et al, 2020;Pitel et al, 2013;Sichert-Hellert et al, 2011;Souza Santos et al, 2019;Tarabashkina et al, 2016;Videon & Manning, 2003) and the home learning environment in 10 studies (Brooks & Begley, 2014;do Amaral e Melo et al, 2020;Garrido-Fernández et al, 2020;Hanson et al, 2004;Lake et al, 2004;Mokhtari et al, 2017;Orehek & Ferrer, 2018;Sanchez et al, 2007;Utter et al, 2013;Videon & Manning, 2003). Bailey, et al (2019).…”
Section: Sample: 13 Studies Includedmentioning
confidence: 99%
“…Four of the six knowledge synthesis studies applied frameworks; PRISMA (n=4/28) (Bailey et al, 2019;do Amaral e Melo et al, 2020;Fleary et al, 2018;Vaitkeviciute et al, 2014) and PICOS (n=1/28) (Bailey et al, 2019).…”
Section: Samplementioning
confidence: 99%